TINDAK TUTUR NEGOSIASI BERMAIN PERAN SISWA KELAS XPEMASARAN SMK KRISTEN IMMANUEL SUNGAI RAYA - Ria, Fitria; Saman, Sisilya; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract       This research was motivated by the interest to know the acts of speech contained in the role play of students of class X Pm 2 SMK Kristen Immanuel II.A common problem in this research is how does the act of speech negotiation play the role of students of class X Pm 2 SMK Kristen Immanuel II? The subproblems are: how does speech act locution, ilokusi, and perlokusi.The method used in this research is descriptive method. This form of research is qualitative. The research data was collected by using the technique of referring. The data is listened by using the help of recorder and recorder. Meanwhile, the analysis of data used is through the criteria of the form of speech acts. Sources of data in this study is the act of speech negotiation play the role of class X students of SMK Kristen Immanuel II. Based on the data of this research, it is concluded that the act of speech contained in playing the role of the negotiation of the students of class X Pm 2 SMK Kristen Immanuel II is the act of speech of locusi, ilokusi, and perlokusi.Keywords: speech acting act, illocution, and perlocution.